2011
DOI: 10.1017/s1474746410000588
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming the Disability Equality Duty and the Impact on Public Authorities' Working Practices

Abstract: Implemented as part of the 2005 amendments to the Disability Equality Act, the Disability Equality Duty (DED) placed new and important demands on public sector bodies. All such organisations are required to develop policies and working practices which actively promote the equality of disabled people as employees, consumers or visitors. The promotion of equality has to be proactive as opposed to reactive and must be mainstreamed into the normal day to day activities of organisational working practices. Whilst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This approach to mainstreaming disability inclusion as a strategy for development and promotion of equality is well cited in the literature, has roots within gender inclusion [35] and is increasingly well adopted at policy level. Miller and Albert [36] discuss key lessons that could be taken from gender mainstreaming and applied to disability mainstreaming within development [36].…”
Section: Disability Inclusive International Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach to mainstreaming disability inclusion as a strategy for development and promotion of equality is well cited in the literature, has roots within gender inclusion [35] and is increasingly well adopted at policy level. Miller and Albert [36] discuss key lessons that could be taken from gender mainstreaming and applied to disability mainstreaming within development [36].…”
Section: Disability Inclusive International Developmentmentioning
confidence: 99%
“…However, the paper revealed limited evidence to suggest disability equality was fully embraced and integrated throughout the organisations analysed. Authors concluded an improved need for a systematic approach to identify and address inequality [35].…”
Section: Previous Studies Of Disability Inclusionmentioning
confidence: 99%
“…What there is considerable evidence for is that disability employment law has improved the circumstances-including in terms of distribution and recognition-of particular individuals included in studies and improved practice in studied organisations, and there is far less published evidence of it having worsened circumstances or practice. Provisions which appear to have made a particular difference include the Disability Equality Duty (DED) (e.g., [36], p. 249) and the Reasonable Adjustments Duty. As regards the Reasonable Adjustments Duty, which is the principal focus of this paper, there is a good deal of evidence (e.g., [37], pp.…”
Section: The Impact Of Disability Discrimination Lawmentioning
confidence: 99%